(untitled) (Práxis Educativa, 2021)
This article presents the contributions of Paulo Freire’s thinking to Media and Education studies and the construction of the concept of Educommunication. For this purpose, a mapping of scientific productions on the theme in Latin America was carried out, with the aim of raising the main fundamentals and recurrent authors in the publications analyzed and their articulation with Freire’s assumptions in the field of Media-Education. It was a qualitative study, whose methodological path included systematic and integrative reviews of selected articles in the Scientific Electronic Library Online (SciELO) database from 2011 to 2019. The discussion signals that the educommunicative field and its multidisciplinary performance emerged and was consolidated from Paulo Freire’s assumptions about communication/education interface and was developed through public policies and school practices that aimed at the emancipation of the subject. Keywords: Paulo Freire. Media-Education. Educommunication.